Future Directions of Credentialing Research in Nursing: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
The nurse workforce constitutes the largest sector of health professionals in the United States and includes individuals with varying educational backgrounds and expertise. Like other health professions, nursing includes a large number of specialties and subspecialties. Nurses may seek certification, based on various standards and criteria, from a wide range of organizations. Similarly, organizations may participate in nursing credentialing programs, which typically reflect the attainment of various nursing care standards and outcome measures. It is, however, unclear how this additional training and education affects health care quality and patient health. Future Directions of Credentialing Research in Nursing examines short- and long-term strategies to advance research on nurse certification and organizational credentialing. This report summarizes a workshop convened by the Institute of Medicine in September 2014 to examine a new framework and research priorities to guide future research on the impact of nurse credentialing and certification on outcomes for nurses, organizations, and patients. Over 100 people attended the workshop, which focused on topics such as emergent priorities for research in nursing credentialing; critical knowledge gaps and methodological limitations in the field; promising developments in research methodologies, health metrics, and data infrastructures to better evaluate the impact of nursing credentialing; and short- and long-term strategies to encourage continued activity in nursing credentialing research. Future Directions of Credentialing Research in Nursing is a record of the presentations, discussion, and break-out sessions of this event.

Keeping Patients Safe: Transforming the Work Environment of Nurses - Institute of Medicine (The National Academies Press, 2004)
Building on the revolutionary Institute of Medicine reports To Err is Human and Crossing the Quality Chasm, Keeping Patients Safe lays out guidelines for improving patient safety by changing nurses' working conditions and demands. Licensed nurses and unlicensed nursing assistants are critical participants in our national effort to protect patients from health care errors. The nature of the activities nurses typically perform 2013 monitoring patients, educating home caretakers, performing treatments, and rescuing patients who are in crisis 2013 provides an indispensable resource in detecting and remedying error-producing defects in the U.S. health care system. During the past two decades, substantial changes have been made in the organization and delivery of health care 2013 and consequently in the job description and work environment of nurses. As patients are increasingly cared for as outpatients, nurses in hospitals and nursing homes deal with greater severity of illness. Problems in management practices, employee deployment, work and workspace design, and the basic safety culture of health care organizations place patients at further risk. This newest edition in the groundbreaking Institute of Medicine Quality Chasm series discusses the key aspects of the work environment for nurses and reviews the potential improvements in working conditions that are likely to have an impact on patient safety.

Assessing Progress on the Institute of Medicine Report The Future of Nursing - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Nurses make up the largest segment of the health care profession, with 3 million registered nurses in the United States. Nurses work in a wide variety of settings, including hospitals, public health centers, schools, and homes, and provide a continuum of services, including direct patient care, health promotion, patient education, and coordination of care. They serve in leadership roles, are researchers, and work to improve health care policy. As the health care system undergoes transformation due in part to the Affordable Care Act (ACA), the nursing profession is making a wide-reaching impact by providing and affecting quality, patient-centered, accessible, and affordable care. In 2010, the Institute of Medicine (IOM) released the report The Future of Nursing: Leading Change, Advancing Health, which made a series of recommendations pertaining to roles for nurses in the new health care landscape. This current report assesses progress made by the Robert Wood Johnson Foundation\/AARP Future of Nursing: Campaign for Action and others in implementing the recommendations from the 2010 report and identifies areas that should be emphasized over the next 5 years to make further progress toward these goals.

National Plan for Health Workforce Well-Being - National Academy of Medicine (The National Academies Press, 2024)
In the United States, 54% of nurses and physicians, 60% of medical students and residents, and 61% of pharmacists have symptoms of burnout. Burnout is a long-standing issue and a fundamental barrier to professional well-being. It was further exacerbated by the COVID-19 pandemic. Health workers who find joy, fulfillment, and meaning in their work can engage on a deeper level with their patients, who are at the heart of health care. Thus, a thriving workforce is essential for delivering safe, high-quality, patient-centered care. The National Plan for Health Workforce Well-Being is intended to inspire collective action that focuses on changes needed across the health system and at the organizational level to improve the well-being of the health workforce. As a nation, we must redesign how health is delivered so that human connection is strengthened, health equity is achieved, and trust is restored. The National Plan2019s vision is that patients are cared for by a health workforce that is thriving in an environment that fosters their well-being as they improve population health, enhance the care experience, reduce costs, and advance health equity; therefore, achieving the 201cquintuple aim.201d Together, we can create a health system in which care is delivered joyfully and with meaning, by a committed team of all who work to advance health, in partnership with engaged patients and communities.

Taking Action Against Clinician Burnout: A Systems Approach to Professional Well-Being - National Academy of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Patient-centered, high-quality health care relies on the well-being, health, and safety of health care clinicians. However, alarmingly high rates of clinician burnout in the United States are detrimental to the quality of care being provided, harmful to individuals in the workforce, and costly. It is important to take a systemic approach to address burnout that focuses on the structure, organization, and culture of health care. Taking Action Against Clinician Burnout: A Systems Approach to Professional Well-Being builds upon two groundbreaking reports from the past twenty years, To Err Is Human: Building a Safer Health System and Crossing the Quality Chasm: A New Health System for the 21st Century, which both called attention to the issues around patient safety and quality of care. This report explores the extent, consequences, and contributing factors of clinician burnout and provides a framework for a systems approach to clinician burnout and professional well-being, a research agenda to advance clinician well-being, and recommendations for the field.

The National Imperative to Improve Nursing Home Quality: Honoring Our Commitment to Residents, Families, and Staff - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Nursing homes play a unique dual role in the long-term care continuum, serving as a place where people receive needed health care and a place they call home. Ineffective responses to the complex challenges of nursing home care have resulted in a system that often fails to ensure the well-being and safety of nursing home residents. The devastating impact of the COVID-19 pandemic on nursing home residents and staff has renewed attention to the long-standing weaknesses that impede the provision of high-quality nursing home care. With support from a coalition of sponsors, the National Academies of Sciences, Engineering, and Medicine formed the Committee on the Quality of Care in Nursing Homes to examine how the United States delivers, finances, regulates, and measures the quality of nursing home care. The National Imperative to Improve Nursing Home Quality: Honoring Our Commitment to Residents, Families, and Staff identifies seven broad goals and supporting recommendations which provide the overarching framework for a comprehensive approach to improving the quality of care in nursing homes.

The Future of Nursing: Leading Change, Advancing Health - Institute of Medicine (The National Academies Press, 2011)
The Future of Nursing explores how nurses' roles, responsibilities, and education should change significantly to meet the increased demand for care that will be created by health care reform and to advance improvements in America's increasingly complex health system. At more than 3 million in number, nurses make up the single largest segment of the health care work force. They also spend the greatest amount of time in delivering patient care as a profession. Nurses therefore have valuable insights and unique abilities to contribute as partners with other health care professionals in improving the quality and safety of care as envisioned in the Affordable Care Act (ACA) enacted this year. Nurses should be fully engaged with other health professionals and assume leadership roles in redesigning care in the United States. To ensure its members are well-prepared, the profession should institute residency training for nurses, increase the percentage of nurses who attain a bachelor's degree to 80 percent by 2020, and double the number who pursue doctorates. Furthermore, regulatory and institutional obstacles2014including limits on nurses' scope of practice2014should be removed so that the health system can reap the full benefit of nurses' training, skills, and knowledge in patient care. In this book, the Institute of Medicine makes recommendations for an action-oriented blueprint for the future of nursing.

Empowering Women and Strengthening Health Systems and Services Through Investing in Nursing and Midwifery Enterprise: Lessons from Lower-Income Countries: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In September 2014, the Global Forum on Innovation in Health Professional Education and the Forum on Public-Private Partnerships for Global Health and Safety of the Institute of Medicine convened a workshop on empowering women and strengthening health systems and services through investing in nursing and midwifery enterprise. Experts in women's empowerment, development, health systems' capacity building, social enterprise and finance, and nursing and midwifery explored the intersections between and among these domains. Innovative and promising models for more sustainable health care delivery that embed women's empowerment in their missions were examined. Participants also discussed uptake and scale; adaptation, translation, and replication; financing; and collaboration and partnership. Empowering Women and Strengthening Health Systems and Services Through Investing in Nursing and Midwifery Enterprise summarizes the presentations and discussion of the workshop. This report highlights examples and explores broad frameworks for existing and potential intersections of different sectors that could lead to better health and well-being of women around the world, and how lessons learned from these examples might be applied in the United States.

A Summary of the October 2009 Forum on the Future of Nursing: Acute Care - Institute of Medicine (The National Academies Press, 2010)
The Robert Wood Johnson Foundation Initiative on the Future of Nursing, at the IOM, seeks to transform nursing as part of larger efforts to reform the health care system. The first of the Initiative's three forums was held on October 19, 2009, and focused on safety, technology, and interdisciplinary collaboration in acute care.

A Summary of the December 2009 Forum on the Future of Nursing: Care in the Community - Institute of Medicine (The National Academies Press, 2010)
The Robert Wood Johnson Foundation Initiative on the Future of Nursing, at the IOM, seeks to build a blueprint for the future of nursing as part of larger efforts to reform the health care system. The second of the Initiative's three forums was held on December 3, 2009, and examined care in the community, focusing on community health, public health, primary care, and long-term care.

A Summary of the February 2010 Forum on the Future of Nursing: Education - Institute of Medicine (The National Academies Press, 2010)
As the U.S. health care system continues to evolve, the role of nurses also needs to evolve. Nurses must strike a delicate balance among advancing science, translating and applying research, and caring for individuals and families across all settings. Preparing nurses to achieve this balance is a significant challenge. The education system should ensure that nurses have the intellectual capacity, human responsiveness, flexibility, and leadership skills to provide care and promote health whenever and wherever needed. Education leaders and faculty need to prepare nurses with the competencies they need now and in the future. They need to prepare nurses to work and assume leadership roles not just in hospitals, but in communities, clinics, homes, and everywhere else nurses are needed. On February 22, 2010 the Initiative on the Future of Nursing held the last public forum in a series of three at the University of Texas MD Anderson Cancer Center. This forum, which covered the education of nurses, consisted of three armchair discussions. Each discussion was led by a moderator from the committee and focused on three broad, overlapping subjects: what to teach, how to teach, and where to teach. The verbal exchange among the discussants and moderators, prompted by additional questions from committee members at the forum, produced a wide-ranging and informative examination of questions that are critical to the future of nursing education. Additionally, testimony presented by 12 individuals and comments made by members of the audience during an open microphone session provided the committee with valuable input from a range of perspectives.

The Future of Nursing 2020-2030: Charting a Path to Achieve Health Equity - National Academy of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The decade ahead will test the nation's nearly 4 million nurses in new and complex ways. Nurses live and work at the intersection of health, education, and communities. Nurses work in a wide array of settings and practice at a range of professional levels. They are often the first and most frequent line of contact with people of all backgrounds and experiences seeking care and they represent the largest of the health care professions. A nation cannot fully thrive until everyone - no matter who they are, where they live, or how much money they make - can live their healthiest possible life, and helping people live their healthiest life is and has always been the essential role of nurses. Nurses have a critical role to play in achieving the goal of health equity, but they need robust education, supportive work environments, and autonomy. Accordingly, at the request of the Robert Wood Johnson Foundation, on behalf of the National Academy of Medicine, an ad hoc committee under the auspices of the National Academies of Sciences, Engineering, and Medicine conducted a study aimed at envisioning and charting a path forward for the nursing profession to help reduce inequities in people's ability to achieve their full health potential. The ultimate goal is the achievement of health equity in the United States built on strengthened nursing capacity and expertise. By leveraging these attributes, nursing will help to create and contribute comprehensively to equitable public health and health care systems that are designed to work for everyone. The Future of Nursing 2020-2030: Charting a Path to Achieve Health Equity explores how nurses can work to reduce health disparities and promote equity, while keeping costs at bay, utilizing technology, and maintaining patient and family-focused care into 2030. This work builds on the foundation set out by The Future of Nursing: Leading Change, Advancing Health (2011) report.